Invasive Cardiac Aspergillosis after Orthotopic Liver Transplantation - Wiltberger, G.; Schmelzle, M.; Schubert, S.; Lübbert, C.; Brandmaier, P.; Berg, T.; Pfeiffer, D.; Rodloff, A.; Mohr, F.-W.; Jonas, S. (Zeitschrift für Gastroenterologie, 2014)
Invasive aspergillus infection occurs in 5 – 42 % of liver-transplanted recipients and is a dangerous complication, associated with high mortality if untreated. However, the early diagnosis of invasive aspergillosis can be elusive, as clinical signs are unspecific and the pathogenic agent is difficult to demonstrate. We here report about a 58-year-old man with acute liver failure caused by newly diagnosed chronic hepatitis B infection who underwent liver transplantation. The postoperative course was uneventful, and the patient was discharged after 30 days. After 105 days the patient was readmitted because of fever, recurrent chest and abdominal pain. Computed tomography revealed a cardiac lesion; other diagnostic steps including bone-marrow and endomycordial biopsy, virological and microbiological investigations gave no clear findings. To exclude a malignant process, thoracotomy with mass and simultaneous lower left lobe resection were performed. Histopathological findings revealed an invasive perimyocardial aspergillosis. Immediate intravenous therapy with voriconazole and caspofungin was initiated and monitoring of the mass was performed with transesophageal echocardiography and Cardio-MRI. Due to slightly increase of the lesion, medication was switched to posaconazole and caspofungin. Under this dual fungal treatment the lesion regressed and the patient could be discharged after two months in good clinical condition. Frequent Cardio-MRI scan after discharge showed further mass-regression. Therefore antifungal treatment was switched to oral posaconazole mono-therapy. After one year, complete reduction of the mass was achieved and antifungal therapy was discontinued. Recent diagnostic imaging follow-up showed no pathological finding.
Keywords: Leber; Transplantation; Hepatitis B; Aspergillose